Role of aluminium paint on the management of peristomal skin excoriation . A case.control study - Ranendra Hajong (Journal of Minimal Access Surgery, 2022)
Introduction: Peristomal skin excoriation is the most common complication of any stoma, especially of ileostomy and entero-cutaneous fistula. Effluent is erosive to skin and at times leads to excoriation of skin and pain or discomfort to the patient. Many strategies or local medications are being used to treat excoriated skin and give comfort to the patient. Aluminium paint is a cheap and effective means of managing skin excoriation. Materials and Methods: This case-control study was conducted in NEIGRIHMS from January 2015 to October 2020 on the role of aluminium paint for the management of skin excoriations due to stoma and fistula. A total of 19 patients were managed with aluminium paint and compared with the data of 19 other patients who were managed by conventional dressings as controls. Results: Aluminium paint helped in the earlier healing of skin excoriations and give comfort to the patients as compared to normal dressings. Conclusion: Aluminium paint is safe and cost-effective skin barrier to prevent and to manage skin excoriations.